Path Analysis : Public Health Impacts Overview in High Natural Background Radiation Area in Botteng, West Sulawesi of Indonesia - Fikri, Elanda; Puspitasari, Evan; Khair, Amar Sharaf Eldin (Faculty of Public Health, Universitas Diponegoro, Semarang, Indonesia, 2022)
Introduction: The effect of ionizing radiation exposure in a human being is chromosome aberrations. Botteng has the highest annual radiation exposure rate in Indonesia, which is 6,15 ± 0,81 mSv/year. The people in Botteng were exposed to the low dose radiation, continuously. The purpose of this research is to describe the pathway radiation exposured to inhabitants and the cytogenetic response in the high natural background radiation area.Methods : This is a statistical research by cross-sectional. The population is 61 residents, who were chosen randomly from 9 different exposure rate areas. Path analysis model is used to determine the linearity relationship between internal and external radiation dose to the frequency of chromosomal aberrations in lymphocyte cells.Results: The results concluded that the external radiation dose rate is 5.49 mSv / year, the internal radiation dose rate is 10.34 mSv / year, the effective dose rate of lymphocyte cells is 1.92 mSv / year, and the mean of chromosome aberrations frequency is 0.00082 of approximately 14,695 metaphase cells observed. The result of the analysis showed that there was no significant correlation between the external dose and the chromosome aberrations frequency. There is a linear relationship between the internal dose and the chromosome aberrations frequency (f count = 6,634 and p-value 0,013 <0,05). The internal and external radiation dose simultaneously affects the effective dose (R2 = 0.901, p-value = 0,000> 0.05), The Internal and external radiation doses affect the chromosome aberrations frequency of peripheral blood lymphocytes only through effective doses (R2 = 0.093, p-value = 0.017> 0.05)Conclusion: this study provide an effective recommendation for further research as an effort to improve public health in areas with high natural background radiation.